2019
DOI: 10.1111/jvim.15635
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term impact of tylosin on fecal microbiota and fecal bile acids of healthy dogs

Abstract: Background: Tylosin is commonly prescribed to dogs with diarrhea. Orally administered antibiotics may alter the intestinal microbiota, which is responsible for crucial key bile acid (BA) biotransformation reactions.Objectives: To prospectively evaluate the impact of tylosin administration on fecal microbiota and unconjugated bile acids (UBAs) over time.Animals: Sixteen healthy adult dogs.Methods: Prospective, randomized controlled clinical trial. Dogs were randomized to receive 20 mg/kg of tylosin or a placebo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
98
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(112 citation statements)
references
References 57 publications
10
98
1
3
Order By: Relevance
“…Since Enterococcus spp. have been reported to develop resistance to TYL [9,10,57], an increase of these bacteria favored by this antibiotic would have been expected in the present study, according to previous trials in the dog, where the proliferation of this potentially probiotic bacterial group was interpreted as a consequence of a potential selective pressure exerted by TYL on the intestinal microbiota both in healthy [7,11] and pathological conditions [8]. The opposite results highlighted during the present study induce to suppose that the response of enterococci towards the presence of TYL might have been influenced by the specific "in vitro" conditions here set up.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Since Enterococcus spp. have been reported to develop resistance to TYL [9,10,57], an increase of these bacteria favored by this antibiotic would have been expected in the present study, according to previous trials in the dog, where the proliferation of this potentially probiotic bacterial group was interpreted as a consequence of a potential selective pressure exerted by TYL on the intestinal microbiota both in healthy [7,11] and pathological conditions [8]. The opposite results highlighted during the present study induce to suppose that the response of enterococci towards the presence of TYL might have been influenced by the specific "in vitro" conditions here set up.…”
Section: Discussionsupporting
confidence: 70%
“…Previous studies based on 16S rRNA sequencing techniques have reported marked changes both in jejunal [7] and fecal [11] microbiota of healthy dogs after TYL treatment, in particular, with a significant decrease in mean bacterial diversity and a reduction of the relative abundance of the most important bacterial taxa.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Recent investigations showed a profound effect of metronidazole and tylosin on the microbiota. Tylosin significantly increased the DI during treatment, and the abundance of Faecalibacterium was significantly decreased after treatment 46 . Also, treatment with metronidazole in dogs leads to significant alterations in the intestinal microbiome with decreased abundances of the taxa Bacteroidaceae , Clostridiaceae , Fusobacteriaceae , Lachnospiraceae , Ruminococcaceae , Turicibacteraceae , and Veillonellaceae and increased abundances of Bifidobacteriaceae , Enterobacteriaceae , Enterococcaceae , and Streptococcaceae 27 …”
Section: Discussionmentioning
confidence: 98%
“…Very recently, as found in healthy dogs, it was shown that the administration of tylosin (20 mg/kg PO BID) induced dysbiosis-and eubiosis was not restored by 56 days following tylosin discontinuation, leading the authors to conclude that in these patients "… reestablishment of the native microbiota is possible but not guaranteed." (Manchester et al 2019). Faecal bacterial diversity was also reduced when administering oral metronidazole for 14 days (12.5 mg/kg BID) to healthy dogs (Igarashi et al 2014).…”
Section: Effects Of Antibacterials On Gi Microbiotamentioning
confidence: 97%